Pencegahan Candaan Berbahaya Melalui Penguatan Budaya Literasi di SDN 042 Kualu - Puti Mayang Seruni; Ersaliya Arezah; Ellydar Chaidir; Nur Aisyah Thalib; Rahima Azzahra; Helen Tesalonika Pasaribu (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2025)
Underage children whose minds are not yet mature are prone to doing things detrimental to themselves and others. The cause is the uncontrolled use of gadgets. The large amount of jokes or 'pranks' content children consume from the internet makes students of SDN 042 Kualu do the same. The solution offered here is to provide socialization and discussion with teachers on how to handle this behavior and the possible legal consequences. Second, a reading corner in the classroom should be built to apply a literacy culture at SDN 042 Kualu. The purpose of this activity is so that students can divert their energy to reading books, gain broad insight, and build noble character through a literacy culture. The method of this activity starts from the preparation and material creation stage, the socialization stage, and the reading corner arrangement stage. The results of this activity are increased insight for teachers, establishing a literacy culture at SDN 042 Kualu, and students no longer joking beyond the limit.